Non-gelated polymeric photonic crystal films - Chu, Zhaoran; Ding, Zheng; Ning, Xuanjun; A, Yimihan; Wang, Menghan; Shao, Kan; Tang, Wenwei; Chen, Cheng; Bai, Jianzhong (Frontiers in Chemistry, 2022)
A rapid curing method for the preparation of colloidal photonic crystal films is presented. Firstly, a colloidal crystal array template was prepared by self-assembly of nanospheres, and then a dilute polymer solution was poured into the gap of the template. Then the composite photonic film was obtained as the polymer solution was cured. Such film has good properties in mechanical strength, anti pH interference, rapid solvent response and is easy to preserve. The film showed a good linear response to ethanol aqueous solutions of different concentrations, and the response equilibrium takes less than 20 s. The film also showed long-term stability and reusability, and further functionalization can make the film multi-sensitive.